First records of scinax ruberoculatus ferrão, fraga, moravec, kaefer & lima, 2018 (Anura, hylidae) in the state of amapá, eastern amazon, Brazil, with comments on its vocalization and distribution - Campos, Carlos Eduardo Costa; Lima, Janaína Reis Ferreira; Lima, Jucivaldo Dias; Santos, Joandro P. dos; Sousa, Jackson Cleiton; Sanches, Patrick Ribeiro; Santos, Fillipe Pedroso; Lopes, André Gomes; Pinheiro, Rodrigo Tavares; Figueiredo, Vinícius Antônio Martins Barbosa de (Check List, 2021)
We report the first records of Scinax ruberoculatus Ferrão, Fraga, Moravec, Kaefer & Lima, 2018 in the state of Amapá, Brazil. We provide an updated distribution map of this species, comment on its occurrence in French Guiana and Suriname, and provide morphometric and bioacoustic data for a population from the municipality of Porto Grande, Amapá, including the first description of the species’ territorial call. This record from Porto Grande extends the distribution of S. ruberoculatus approximately 1430 km northeast from its type locality and helps to better understand its actual distribution. © The authors.
Keywords: Advertisement call; Bioacoustics; Guiana Shield; Morphometric measurements; Range extension; Territorial call